Temporal expression of defense-related genes in Ganoderma-infected oil palm roots - Mohan, Durgadevi; Namasivayam, Parameswari; Saidi, Noor Baity; Ho, Chai Ling (Springer, 2022)
Basal stem rot is an oil palm disease which causes substantial loss to the oil palm industry in Southeast Asia. Temporal gene expression analysis of oil palms infected with Ganoderma boninense is important to identify the defense pathways at biotrophic and necrotrophic phases of fungal infection. The aim of this study was to analyze the gene expression of oil palm genes related to respiratory burst oxidation, phytohormone biosynthesis, salicylic acid- and jasmonic acid-mediated defense pathways in oil palm roots infected by G. boninense at different time points. The findings of this study confirmed that salicylic acid mediated the early defense response from infected oil palm during the biotrophic phase of fungal infection, while the JA-mediated defense response was triggered when the root lesions occurred in the infected oil palm root tissues during the necrotrophic phase of Ganoderma infection. The oil palm defense responses may play a role in delaying the progression of basal stem rot but is insufficiently effective to eradicate Ganoderma infection. Temporal gene expression may help in finding methods to ameliorate the impact of basal stem rot by prolonging the productive lifespan of diseased trees and to reduce the economic loss due to this disease.